Edukasi Etika Bisnis Pengelolaan Usaha pada UMKM Desa Bugis Kecamatan Sape Kabupaten Bima - Kartin Aprianti; Puji Rahayu; Syrilus Alexander Alvaro Roja (FKIP, Universitas Palangka Raya, 2025)
Doing business, big or small, is bound by ethical issues. Ethics refer to what a person should do morally. The partners of the PKM activity are SMEs engaged in creative craft products made of acrylic/mute and knitted materials. located in Serang Banten. The PKM activity aims to provide knowledge to partners about business ethics that partners need to have in doing business. plus the partner's business is located in a densely populated area. It is necessary to maintain ethical behavior where the partner's business is located. the method offered to partners/SMEs is in the form of education/socialization using LEAFLET which is carried out door to door. . The material provided in the leaflet includes a discussion of the Role of Ethics in doing business for SME actors, Benefits of doing business for SME actors Application of ethical principles in doing business in financial, marketing, production and HR activities. The results of the activity showed that partners were very enthusiastic in listening and discussing during the activity. In addition, it can provide knowledge about ethics in running a business.